The impact of terrorism and conflicts on growth in Asia, 1970- 2004 - Khusrav Gaibulloev; Todd Sandler (Asian Development Bank Institute (ADBI), 2008)
This paper quantifies the impact of terrorism and conflicts on income per capita growth in Asia for 1970-2004. Our panel estimations show that transnational terrorist attacks had a significant growth-limiting effect. An additional terrorist incident per million persons reduces gross domestic product (GDP) per capita growth by about 1.5%. In populous countries, many additional attacks are needed to achieve such a large impact. Transnational terrorism reduces growth by crowding in government expenditures. Unlike developing countries, developed countries are able to absorb terrorism without displaying adverse economic consequences; an internal conflict has the greatest growth concern, about twice that of transnational terrorism. Conflict variables are associated with smaller investment shares and increased government spending, with the crowding in of government spending being the dominant influence. For developing Asian countries, intrastate and interstate wars have a much greater impact than terrorism does on the crowding-in of government spending. When regime types-democratic and autocratic-are taken into account, in our research, we found that the precision of the estimates increases with the increasing significance of transnational terrorist attacks. Policy recommendations indicate the need for rich Asian countries to assist their poorer neighbors in coping with the negative growth consequences of political violence. Failure to assist may result in region-wide repercussions. This is particularly relevant as production becomes fragmented in Asia in order to profit from comparative advantage and as regional infrastructure networks link Asia to exploit scale economies. In the latter case, conflict and terrorism in one country can create bottlenecks with region-wide economic consequences. Moreover, prime-target Western countries-e.g., the United States and the United Kingdom-have a responsibility to bolster Asian defenses against terrorism as attacks against Western interests have been shifted, in part, to Asian venues since the 9/11 attacks in the United States. The Association of South East Asian Nations (ASEAN) and European Union link can assist with coordinating efforts to quell conflicts and eliminate terrorism, but this requires putting recent declarations into practice. The Asian Development Bank and the World Bank could play pivotal roles, especially after a conflict ends, to channel aid for reconstruction so that once-embattled countries can recover rapidly. Nongovernmental organizations and the United Nations could also assist in this post-conflict recovery. The Asian Development Band and ASEAN could coordinate and fund counterterrorism spending to curb overspending on defensive measures and bolster under-spending on proactive measures. The United Nations could assist in peacekeeping operations for internal conflicts.
Keywords: H56; D74; O40; 330; Sozialprodukt; Politische Gewalt; Politischer Konflikt; Asien